The Role of Food Processed Micro, Small and Medium Enterprises (MSMEs) in Reducing Poverty Levels in Gorontalo Province - Mohammad Zubair Hippy; Syarwani Canon; Asda Rauf (Pusat Studi Pembangunan dan Pemberdayaan, 2022)
This study aims to determine the role of food-processed Micro, Small and Medium Enterprises (MSMEs) in reducing poverty levels in Gorontalo Province. This research is a quantitative research. The data source in this study is secondary data obtained through the website of the Central Statistics Agency (BPS) and the Gorontalo Province Food Service. The data analysis used in this study is the Simultaneous Equation / Indirect Least Square. The results of this study indicate that food-processed MSME LQ and labor absorption have a negative and significant effect on the poverty of districts / cities in Gorontalo Province, both simultaneously and partially with a coefficient of determination of 91.372%. The more concentrated food-processed MSMEs are and the higher the labor absorption of food-processed MSMEs, the more they will be able to reduce poverty levels.